Application of Chinese herbal medicine formula in crab and shrimp breeding - HE XIAODONG; HE XIAOJIN; HE ZHIZHONG (2014)
The traditional Chinese medicine formula of honeysuckle, yellow grass, figwort roots, coix seeds, achyranthes bidentata and the like is utilized to serve as feed additives of crabs and shrimps. When the additive amount is 0.3%-3%, the appetite can be increased, growing is promoted, and disease resistance and stress resistance are improved. The yield-increasing effect reaches more than 10%. For the increased expense by using of the additives, the rate of return is 7-12 times.